A long-acting weather-resistant anticorrosive powder coating and a preparation method thereof

CN122941282APending Publication Date: 2026-10-20ZHEJIANG CHAOLANG ADVANCED MATERIALS
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611442983.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-17
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

[0003]然而,粉末涂料在实际户外服役过程中要受到太阳光紫外辐射、温度交变循环、湿气渗透、盐雾侵蚀、酸雨腐蚀以及工业大气中的腐蚀性气体等多重因素的影响,使涂层中的紫外线吸收剂、抗氧剂等助剂发生迁移和挥发损失,最终导致涂层在服役过程中逐渐发生老化降解和防腐性能衰减

Benefits of technology

1、本申请通过在β-环糊精分子中引入环氧丙基和羧甲基基团,不仅提高了β-环糊精与树脂基体之间的相容性和结合强度,而且降低了粉末涂料中抗氧剂和紫外线吸收剂的挥发和迁移,从而提高涂层的耐候防腐长效性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

This application belongs to the field of powder coating technology, specifically providing a long-lasting weather-resistant and anti-corrosion powder coating and its preparation method. The long-lasting weather-resistant and anti-corrosion powder coating comprises the following components: polyester resin, curing agent, modified cyclodextrin, organically modified layered double hydroxide, ultraviolet absorber, antioxidant, titanium dioxide, barium sulfate, leveling agent, and benzoin; the modified cyclodextrin is β-cyclodextrin modified with glycidyl and carboxymethyl groups, which can improve the compatibility with the resin matrix and reduce the volatilization and migration of antioxidants and ultraviolet absorbers; the organically modified layered double hydroxide is a terephthalate-intercalated zinc-aluminum layered double hydroxide, which can improve the long-lasting weather-resistant and anti-corrosion performance of the coating through the maze effect and interlayer adsorption synergistic effect with the modified cyclodextrin.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application belongs to the field of powder coating technology, and in particular relates to a long-lasting weather-resistant and anti-corrosion powder coating and its preparation method. Background Technology

[0002] Powder coatings are powdered coatings composed of solid resins, pigments, fillers, and additives. They are applied to the surface of a substrate through methods such as electrostatic spraying or fluidized bed dipping, and then heated, melted, leveled, and cured to form a dense coating film. Compared with traditional solvent-based coatings, powder coatings have significant advantages such as being solvent-free, having near-zero volatile organic compound emissions, and exhibiting excellent film density. They are widely used in fields such as architectural aluminum profiles, household appliances, automotive parts, bridge steel structures, marine engineering equipment, and oil and gas pipelines.

[0003] However, powder coatings are subject to multiple factors during actual outdoor service, such as solar ultraviolet radiation, temperature cycling, moisture penetration, salt spray erosion, acid rain corrosion, and corrosive gases in the industrial atmosphere. These factors cause the migration and volatilization of additives such as ultraviolet absorbers and antioxidants in the coating, ultimately leading to the gradual aging and degradation of the coating and the decline of its anti-corrosion performance during service.

[0004] To suppress the migration and volatilization loss of additives, the following techniques are commonly used: 1. Bonding functional additives such as UV absorbers and antioxidants to the resin molecular chain through copolymerization or grafting to solve the migration problem. However, this method is complex, costly, and difficult to scale up for industrial application, and it also reduces the aging resistance. 2. Loading additives onto porous carriers or adding sheet-like barrier fillers to slow down the release and migration rate of additives. However, this method suffers from poor compatibility between the carrier and the polymer matrix, limited loading capacity, and uncontrollable release. Therefore, developing a powder coating with long-lasting weather resistance and corrosion protection is of great significance. Summary of the Invention

[0005] To address the aforementioned issues, this application provides a long-lasting weather-resistant and corrosion-resistant powder coating and its preparation method.

[0006] This application first provides a long-lasting weather-resistant and anti-corrosion powder coating, comprising the following components in parts by weight: 55-65 parts polyester resin, 4-6 parts curing agent, 3-8 parts modified cyclodextrin, 1-5 parts organic modified layered bimetallic hydroxide, 0.5-1.5 parts ultraviolet absorber, 0.3-1 part antioxidant, 20-30 parts titanium dioxide, 5-15 parts barium sulfate, 0.5-1.5 parts leveling agent, and 0.3-0.6 parts benzoin; wherein the modified cyclodextrin is β-cyclodextrin modified with glycidyl and carboxymethyl groups.

[0007] Preferably, the ultraviolet absorber is one or more of UV-P, UV-9, and UV-531; and / or, the antioxidant is one or more of antioxidant 264, bisphenol A, and antioxidant 2246.

[0008] Preferably, the preparation method of the modified cyclodextrin includes the following steps: S1: β-Cyclodextrin was dissolved in an organic solvent under nitrogen protection, activated with sodium hydroxide, and epichlorohydrin was slowly added dropwise to carry out the reaction. After precipitation with methanol, washing and drying, epichlorohydrin was obtained. S2: Dissolve glycidyl β-cyclodextrin in water, add monochloroacetic acid, adjust the pH to 10-11, and then react. After precipitation with ethanol, washing, and drying, the product is obtained.

[0009] Preferably, in step S1, the mass ratio of β-cyclodextrin to epichlorohydrin is 1:(0.3-0.4).

[0010] Preferably, in step S2, the mass ratio of epioxypropylated β-cyclodextrin to monochloroacetic acid is 1:(0.1-0.2).

[0011] Preferably, the method for preparing the organically modified layered bimetallic hydroxide includes the following steps: A) Dissolve zinc salt and aluminum salt in water, co-precipitate under alkaline conditions, and obtain the precursor by aging, filtration, washing and drying; B) The precursor is pretreated in sodium chloride solution, then reacted with disodium terephthalate aqueous solution, and obtained by filtration, washing and drying.

[0012] Preferably, in step A), the molar ratio of zinc salt to aluminum salt is (2-3.5):1.

[0013] Preferably, in step B), the concentration of the disodium terephthalate aqueous solution is 0.1-0.5 mol / L.

[0014] This application also provides a method for preparing a long-lasting weather-resistant and anti-corrosion powder coating, comprising the following steps: First, the modified cyclodextrin, ultraviolet absorber, and antioxidant are dispersed in water to obtain an inclusion solution; then, the organic modified layered bimetallic hydroxide is dispersed in water to obtain a suspension; the inclusion solution is added dropwise to the suspension, stirred and reacted, and after filtration, washing, and drying, polyester resin, curing agent, titanium dioxide, barium sulfate, leveling agent, and benzoin are added, mixed evenly, melt-extruded, and then cooled and crushed.

[0015] Preferably, the parameters for melt extrusion are: feeding section temperature of 80-100℃, melting section temperature of 100-120℃, extrusion section temperature of 110-130℃, screw speed of 300-500rpm, and residence time of 30-60s.

[0016] Compared with the prior art, this application has the following beneficial effects: 1. This application improves the compatibility and bonding strength between β-cyclodextrin and the resin matrix by introducing glycidyl and carboxymethyl groups into the β-cyclodextrin molecule, and reduces the volatilization and migration of antioxidants and ultraviolet absorbers in powder coatings, thereby improving the long-term weather resistance and corrosion protection of the coating.

[0017] 2. This application utilizes modified cyclodextrin to encapsulate small molecule substances such as antioxidants and ultraviolet absorbers, thereby reducing the volatilization and migration of the coating during long-term service and improving the long-term weather resistance and corrosion protection of the coating.

[0018] 3. This application enhances the adsorption capacity of additive molecules such as antioxidants and ultraviolet absorbers by introducing terephthalic acid-intercalated zinc-aluminum layered bimetallic hydroxides. At the same time, the nanosheet structure forms a physical barrier, thereby further reducing the volatilization and migration of additive molecules. In addition, modified cyclodextrin can be anchored to the surface and interlayer of the layered bimetallic hydroxides through electrostatic attraction and hydrogen bonding to form a complex. The two interact synergistically to further reduce the volatilization and migration of small molecule additives and reduce the penetration rate of corrosive agents into the substrate, thereby improving the long-term weather resistance and corrosion protection performance of the coating. Attached Figure Description

[0019] Figure 1 To accelerate the retention rate of UV absorbers and antioxidants in the coating after aging.

[0020] Figure 2 To accelerate the gloss retention of the coating after aging. Detailed Implementation

[0021] To make the inventive objectives, technical solutions, and beneficial technical effects of this application clearer, the following detailed description is provided in conjunction with embodiments, clearly and completely describing the technical solutions in the embodiments of this application. Obviously, the described embodiments are merely some embodiments of this application, and not all embodiments. All other embodiments obtained by those skilled in the art based on the embodiments of this application without creative effort are within the scope of protection of this application.

[0022] This application, based on extensive experimental research, provides a long-lasting weather-resistant and anti-corrosion powder coating, comprising the following components in parts by weight: 55-65 parts of polyester resin, for example, 55 parts, 58 parts, 60 parts, 62 parts, or 65 parts; 4-6 parts of curing agent, for example, 4 parts, 4.5 parts, 5 parts, 5.5 parts, or 6 parts; 3-8 parts of modified cyclodextrin, for example, 3 parts, 4 parts, 5 parts, 6 parts, 7 parts, or 8 parts; 1-5 parts of organically modified layered bimetallic hydroxide, for example, 1 part, 1.5 parts, 2 parts, 2.5 parts, 3 parts, 3.5 parts, 4 parts, 4.5 parts, or 5 parts; and 0.5-1.5 parts of ultraviolet absorber, for example, 0.5 parts... 0.8 parts, 1 part, 1.2 parts, 1.5 parts; antioxidant 0.3-1 part, for example, 0.3 parts, 0.5 parts, 0.8 parts, 1 part; titanium dioxide 20-30 parts, for example, 20 parts, 22 parts, 25 parts, 28 parts, 30 parts; barium sulfate 5-15 parts, for example, 5 parts, 8 parts, 10 parts, 12 parts, 15 parts; leveling agent 0.5-1.5 parts, for example, 0.5 parts, 0.8 parts, 1 part, 1.2 parts, 1.5 parts; benzoin 0.3-0.6 parts, for example, 0.3 parts, 0.4 parts, 0.5 parts, 0.6 parts; the modified cyclodextrin is β-cyclodextrin modified with glycidyl and carboxymethyl groups.

[0023] In some embodiments of this application, firstly, ultraviolet absorber and antioxidant auxiliaries can be encapsulated in the hydrophobic cavity of cyclodextrin molecules to form an inclusion complex. Then, the modified cyclodextrin can firmly anchor the inclusion complex on the surface and between the layers of the organic modified layered bimetallic hydroxide through electrostatic attraction and hydrogen bonding with the hydroxyl groups of the layers, further reducing the migration and volatilization of ultraviolet absorber and antioxidant auxiliaries.

[0024] In some embodiments of this application, the ultraviolet absorber is one or more of UV-P, UV-9, and UV-531; and / or, the antioxidant is one or more of antioxidant 264, bisphenol A, and antioxidant 2246.

[0025] In some embodiments of this application, the method for preparing the modified cyclodextrin includes the following steps: S1: β-Cyclodextrin was dissolved in an organic solvent under nitrogen protection, activated with sodium hydroxide, and epichlorohydrin was slowly added dropwise to carry out the reaction. After precipitation with methanol, washing and drying, epichlorohydrin was obtained. S2: Dissolve glycidyl β-cyclodextrin in water, add monochloroacetic acid, adjust the pH to 10-11, and then react. After precipitation with ethanol, washing, and drying, the product is obtained.

[0026] In some embodiments of this application, the β-cyclodextrin molecule contains a large number of hydroxyl groups and has high crystallinity. If it is directly mixed with polyester resin, the compatibility is poor, and it will react uncontrollably with polyester resin during melting, resulting in a sudden increase in the viscosity of the extruded material, causing local pre-crosslinking, and may also destroy the cavity structure of β-cyclodextrin, leading to cavity collapse and reduced inclusion capacity.

[0027] This application introduces epoxypropyl groups into β-cyclodextrin, which not only allows it to react with polyester resins or curing agents to graft β-cyclodextrin into the polymer network, reducing the volatility and migration of small molecule additives encapsulated by β-cyclodextrin and improving weather resistance and long-lasting performance, but also breaks the intermolecular crystallization and strong hydrogen bond network of β-cyclodextrin, reducing its crystallinity and polarity, and improving its compatibility with polyester resins.

[0028] This application improves the compatibility with polyester resin by introducing carboxymethyl groups into β-cyclodextrin. Furthermore, during curing and service, the carboxyl groups can coordinate with metal ions on the surface of the metal substrate, enhancing the adhesion between the coating and the metal interface, inhibiting the interfacial penetration of corrosive media, and improving the anti-corrosion performance of the coating.

[0029] In some embodiments of this application, in step S1, the mass ratio of β-cyclodextrin to epichlorohydrin is 1:(0.3-0.4), for example, it can be 1:0.3, 1:0.32, 1:0.35, 1:0.38, or 1:0.4.

[0030] In some embodiments of this application, in step S2, the mass ratio of epioxypropylated β-cyclodextrin to monochloroacetic acid is 1:(0.1-0.2), for example, it can be 1:0.1, 1:0.12, 1:0.15, 1:0.18, or 1:0.2.

[0031] In some embodiments of this application, the method for preparing the organically modified layered bimetallic hydroxide includes the following steps: A) Dissolve zinc salt and aluminum salt in water, co-precipitate under alkaline conditions, and obtain the precursor by aging, filtration, washing and drying; B) The precursor is pretreated in sodium chloride solution, then reacted with disodium terephthalate aqueous solution, and obtained by filtration, washing and drying.

[0032] In some embodiments of this application, a terephthalate-intercalated zinc-aluminum layered bimetallic hydroxide is employed. The rigid aromatic ring structure of terephthalic acid not only expands the interlayer spacing, providing more space for the adsorption of modified cyclodextrin and auxiliary agent molecules, but also allows for π-π stacking interactions with the aromatic rings in the auxiliary agent molecules, enhancing the adsorption capacity and thus slowing down the volatilization and migration of auxiliary agent molecules. Furthermore, the labyrinth effect of the layered bimetallic hydroxide structure and the hydrogen bond network formed between it and the modified cyclodextrin and resin matrix can also reduce the penetration of corrosive media into the interior, as well as the volatilization and migration of auxiliary agent molecules.

[0033] In some embodiments of this application, in step A), the molar ratio of zinc salt to aluminum salt is (2-3.5):1, for example, it can be 2:1, 2.2:1, 2.5:1, 2.8:1, 3:1, 3.2:1, or 3.5:1.

[0034] In some embodiments of this application, in step B), the concentration of the disodium terephthalate aqueous solution is 0.1-0.5 mol / L, for example, it can be 0.1 mol / L, 0.2 mol / L, 0.3 mol / L, 0.4 mol / L, or 0.5 mol / L.

[0035] This application also provides a method for preparing a long-lasting weather-resistant and anti-corrosion powder coating, comprising the following steps: First, the modified cyclodextrin, ultraviolet absorber, and antioxidant are dispersed in water to obtain an inclusion solution; then, the organic modified layered bimetallic hydroxide is dispersed in water to obtain a suspension; the inclusion solution is added dropwise to the suspension, stirred and reacted, and after filtration, washing, and drying, polyester resin, curing agent, titanium dioxide, barium sulfate, leveling agent, and benzoin are added, mixed evenly, melt-extruded, and then cooled and crushed.

[0036] In some embodiments of this application, the parameters for melt extrusion are as follows: the feeding section temperature is 80-100℃, for example, 80℃, 85℃, 90℃, 95℃, or 100℃; the melting section temperature is 100-120℃, for example, 100℃, 105℃, 110℃, 115℃, or 120℃; the extrusion section temperature is 110-130℃, for example, 110℃, 115℃, 120℃, 125℃, or 130℃; the screw speed is 300-500 rpm, for example, 300 rpm, 350 rpm, 400 rpm, 450 rpm, or 500 rpm; and the residence time is 30-60 s, for example, 30 s, 35 s, 40 s, 45 s, 50 s, 55 s, or 60 s.

[0037] The present application will be further illustrated by the following examples, but these examples do not limit the scope of the present application.

[0038] When numerical ranges are given in the embodiments, it should be understood that, unless otherwise stated in this application, both endpoints of each numerical range and any value between the two endpoints may be selected. Unless otherwise defined, all technical and scientific terms used in this application have the same meaning as commonly understood by one of ordinary skill in the art. Where specific conditions are not specified in the embodiments, conventional conditions or conditions recommended by the manufacturer shall apply. All reagents or instruments whose manufacturers are not specified are conventional products that can be purchased commercially. In addition to the specific methods, equipment, and materials used in the embodiments, based on the knowledge of the prior art possessed by one of ordinary skill in the art and the description in this application, any prior art methods, equipment, and materials similar to or equivalent to those described, used, or made by the methods, equipment, and materials in the embodiments of this application may be used to implement this application.

[0039] Example 1 The long-lasting weather-resistant and anti-corrosion powder coating of this embodiment contains the following components in parts by weight: 60 parts of carboxyl-terminated polyester resin (acid value of approximately 35 mg KOH / g), 5 parts of TGIC curing agent, 5 parts of modified cyclodextrin, 3 parts of organic modified layered bimetallic hydroxide, 1 part of ultraviolet absorber UV-P, 0.6 parts of antioxidant 264, 25 parts of titanium dioxide, 10 parts of barium sulfate, 1 part of leveling agent, and 0.5 parts of benzoin. The method for preparing modified cyclodextrin in this embodiment includes the following steps: S1: 10 g of β-cyclodextrin was dried in a vacuum oven at 100 °C for 12 h to remove water of crystallization. The dried β-cyclodextrin was added to 500 mL of anhydrous dimethyl sulfoxide and stirred and dissolved at 60 °C under nitrogen protection. 2.8 g of sodium hydroxide was added and stirred for 2 h. 3.2 g of epichlorohydrin was slowly added dropwise. After the addition was complete, the reaction was continued for 6 h. After the reaction was completed, the reaction solution was cooled to room temperature and slowly poured into 1000 mL of methanol to precipitate. The precipitate was filtered, washed three times with methanol, and dried under vacuum at 50 °C for 24 h to obtain epioxypropylated β-cyclodextrin. S2: Dissolve 8 g of glycidyl β-cyclodextrin in 400 mL of deionized water, add 1.5 g of monochloroacetic acid, stir at room temperature for 30 min, slowly add 30% NaOH solution to adjust the pH to 10.5, heat to 70℃ and react for 4 h, maintaining the pH at around 10.5 during the reaction. After the reaction is complete, adjust the pH to 7.0 with HCl, slowly pour the reaction solution into 1000 mL of ethanol to precipitate, filter, wash with ethanol-water solution (ethanol to water volume ratio of 4:1), and vacuum dry at 50℃ for 24 h to obtain the product. The method for preparing the organically modified layered bimetallic hydroxide in this embodiment includes the following steps: A) Dissolve 0.10 mol of zinc nitrate hexahydrate and 0.05 mol of aluminum nitrate nonahydrate in 500 mL of deionized water to prepare a mixed salt solution; dissolve 12 g of sodium hydroxide and 2.65 g of sodium carbonate in 500 mL of deionized water to prepare an alkaline solution; under vigorous stirring, slowly add the mixed salt solution and alkaline solution dropwise into a reactor containing 200 mL of deionized water, controlling the dropping rate to maintain the pH of the reaction system at 9.5. After the addition is complete, age the reaction system at 65°C for 24 h. After aging, filter, wash with deionized water until neutral, and vacuum dry at 60°C for 24 h to obtain the precursor. B) Prepare a 0.3 mol / L disodium terephthalate solution; add 10 g of the precursor to 500 mL of a 1 mol / L NaCl solution and stir at room temperature for 24 h for pretreatment. After filtration and washing, add the precursor to 500 mL of the disodium terephthalate solution and stir at 60 °C for 24 h. After the reaction is complete, filter, wash repeatedly with deionized water, vacuum dry at 60 °C for 24 h, and grind through a 200-mesh sieve to obtain the product. The preparation method of the long-lasting weather-resistant and anti-corrosion powder coating in this embodiment includes the following steps: According to the formula ratio, the modified cyclodextrin, UV absorber UV-P, and antioxidant 264 were weighed and dispersed in deionized water, and stirred at 40℃ for 12 hours to form an inclusion complex solution. The organic modified layered bimetallic hydroxide was dispersed in deionized water and ultrasonically dispersed for 30 minutes to form a uniform suspension. Under stirring conditions, the above inclusion complex solution was slowly added dropwise to the organic modified layered bimetallic hydroxide suspension. After the addition was complete, stirring was continued for 6 hours. After the reaction was completed, the mixture was filtered, washed three times with deionized water, and vacuum dried at 50℃ for 24 hours. Then, polyester resin, TGIC curing agent, titanium dioxide, barium sulfate, leveling agent, and benzoin were added and mixed for 5 minutes. The mixed material was added to a twin-screw extruder for melt mixing and extrusion. The extrusion process parameters were: feed section temperature: 90℃, melt section temperature: 110℃, extrusion section temperature: 120℃, screw speed: 400 rpm, residence time: 45s. After the extrudate cooled to room temperature, it was crushed and screened.

[0040] Example 2 The long-lasting weather-resistant and anti-corrosion powder coating of this embodiment contains the following components in parts by weight: 55 parts of carboxyl-terminated polyester resin (acid value of approximately 35 mg KOH / g), 4 parts of TGIC curing agent, 8 parts of modified cyclodextrin, 5 parts of organic modified layered bimetallic hydroxide, 1.5 parts of ultraviolet absorber UV-P, 1 part of antioxidant 264, 25 parts of titanium dioxide, 8 parts of barium sulfate, 1 part of leveling agent, and 0.5 parts of benzoin. The preparation methods of the modified cyclodextrin and organically modified layered bimetallic hydroxide in this embodiment are the same as those in Example 1; The preparation method of the long-lasting weather-resistant and anti-corrosion powder coating in this embodiment is the same as that in Example 1.

[0041] Example 3 The long-lasting weather-resistant and anti-corrosion powder coating of this embodiment contains the following components in parts by weight: 65 parts of carboxyl-terminated polyester resin (acid value of approximately 35 mg KOH / g), 6 parts of TGIC curing agent, 3 parts of modified cyclodextrin, 1 part of organic modified layered bimetallic hydroxide, 0.5 parts of UV absorber UV-P, 0.3 parts of antioxidant 264, 25 parts of titanium dioxide, 12 parts of barium sulfate, 1 part of leveling agent, and 0.5 parts of benzoin; The preparation methods of the modified cyclodextrin and organically modified layered bimetallic hydroxide in this embodiment are the same as those in Example 1; The preparation method of the long-lasting weather-resistant and anti-corrosion powder coating in this embodiment is the same as that in Example 1.

[0042] Comparative Example 1 The long-lasting weather-resistant and anti-corrosion powder coating of this comparative example differs from that of Example 1 in that it does not contain modified cyclodextrin and organically modified layered bimetallic hydroxide. The preparation method of the long-lasting weather-resistant and anti-corrosion powder coating in this comparative example differs from that in Example 1 in that it does not contain modified cyclodextrin and organically modified layered bimetallic hydroxide.

[0043] Comparative Example 2 The long-lasting weather-resistant and anti-corrosion powder coating of this comparative example differs from that of Example 1 in that it does not contain organically modified layered bimetallic hydroxides. The preparation method of the modified cyclodextrin in this comparative example is the same as that in Example 1; The preparation method of the long-lasting weather-resistant and anti-corrosion powder coating in this comparative example differs from that in Example 1 in that it does not contain organically modified layered bimetallic hydroxide.

[0044] Comparative Example 3 The long-lasting weather-resistant and anti-corrosion powder coating of this comparative example differs from that of Example 1 in that it does not contain modified cyclodextrin. The preparation method of the organic modified layered bimetallic hydroxide in this comparative example is the same as that in Example 1; The preparation method of the long-lasting weather-resistant and anti-corrosion powder coating in this comparative example differs from that in Example 1 in that it does not contain modified cyclodextrin.

[0045] Comparative Example 4 The long-lasting weather-resistant and anti-corrosion powder coating of this comparative example differs from that of Example 1 in that it does not contain organic modified layered bimetallic hydroxide and the modified cyclodextrin is replaced with β-cyclodextrin. The preparation method of the long-lasting weather-resistant and anti-corrosion powder coating in this comparative example differs from that in Example 1 in that it does not contain organically modified layered bimetallic hydroxides, and the modified cyclodextrin is replaced with β-cyclodextrin.

[0046] Performance testing Sample preparation: The metal substrate (steel plate) to be coated was degreased, washed with water, phosphated / passivated, and dried in sequence. The powder coatings of Examples 1-3 and Comparative Examples 1-4 were sprayed onto the substrate surface using an electrostatic spray gun. The coating thickness was 60 μm. The curing process was as follows: the temperature was first increased to 120°C at a rate of 5°C / min and held for 5 min, then increased to 180°C at a rate of 10°C / min and held for 15 min. The sample was then allowed to cool naturally to room temperature.

[0047] 1. Adjuvant retention rate test Accurately weigh 0.5 g of coating powder, place it in a Soxhlet extractor, use dichloromethane as the extraction solvent, extract at 60℃ for 6 h, concentrate the extract by rotary evaporation, and determine the contents of ultraviolet absorber UV-P and antioxidant 264 by high performance liquid chromatography as the initial additive content; The coating samples were placed in an accelerated aging test chamber for UV aging. Test conditions: UVA-340 lamp, irradiance 0.89 W / m²·nm, cycle regime: 8 hours of UV irradiation (60℃) → 4 hours of condensation (50℃), total test time 2000 hours. After aging, the remaining additive content was measured. The additive retention rate was calculated using the formula: Additive retention rate = Remaining additive content / Initial additive content × 100%. The results are as follows: Figure 1 As shown.

[0048] from Figure 1 As can be seen, the retention rates of the adjuvants in Examples 1-3 all reached over 84%, which was significantly higher than that in the comparative example. This indicates that the synergistic effect of modified cyclodextrin and organically modified layered bimetallic hydroxides achieved efficient anchoring and retention of UV absorbers and antioxidants.

[0049] 2. Gloss retention test The gloss values ​​of the coatings before and after accelerated aging were measured using a 60° gloss meter. For each sample, measurements were taken at five different locations, and the average value was calculated. The gloss retention rate was calculated using the formula: Gloss Retention Rate = (Gloss after Aging / Initial Gloss) × 100%. The results are as follows: Figure 2 As shown.

[0050] from Figure 2 As can be seen from the data, the gloss retention rate of Examples 1-3 all reached over 85%, indicating that the coating can maintain good appearance and decorative properties after accelerated UV aging.

[0051] 3. Neutral salt spray resistance test The coatings prepared by the powder coatings of Examples 1-3 and Comparative Examples 1-4 were subjected to neutral salt spray resistance tests. The test conditions were: NaCl solution concentration 50±5 g / L, pH 6.5-7.2, test temperature 35±2℃, salt spray deposition 1-2 mL / (80 cm²·h). Cross-shaped scratches (approximately 50 mm in length) were made on the coating surface with a blade, penetrating to the substrate. After continuous spraying for 1000 hours, the samples were taken out, rinsed with tap water, and dried. The unidirectional corrosion width at the scratches and the blistering, rusting, cracking, and peeling in the unscratched areas were evaluated. The results are shown in Table 1.

[0052] 4. Adhesion test According to GB / T 9286-1998, cross-cut adhesion was tested, and dry adhesion (at room temperature) and wet adhesion (the coating sample was soaked in deionized water at 40℃ for 240 hours, then removed, dried and tested immediately). The adhesion grades are shown in Table 1.

[0053] Table 1 Results of coating resistance to neutral salt spray and adhesion tests As shown in Table 1, the unidirectional corrosion width at the scratched areas in Examples 1-3 is ≤1.5 mm, and the unscratched areas remain intact, without blistering, rusting, cracking, or peeling, indicating that the coating has excellent anti-corrosion performance. The dry adhesion of Examples 1-3 is all grade 0, and the wet adhesion is grade 0-1, indicating strong interfacial bonding between the coating and the substrate, and maintaining excellent adhesion even in humid and hot environments.

[0054] Although this application has been described in detail with reference to the foregoing embodiments, those skilled in the art can still modify the technical solutions described in the foregoing embodiments or make equivalent substitutions for some of the technical features. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of this application should be included within the protection scope of this application.

Claims

1. A long-lasting weather-resistant and corrosion-resistant powder coating, characterized in that: The product comprises the following components in parts by weight: 55-65 parts polyester resin, 4-6 parts curing agent, 3-8 parts modified cyclodextrin, 1-5 parts organic modified layered bimetallic hydroxide, 0.5-1.5 parts ultraviolet absorber, 0.3-1 part antioxidant, 20-30 parts titanium dioxide, 5-15 parts barium sulfate, 0.5-1.5 parts leveling agent, and 0.3-0.6 parts benzoin; wherein the modified cyclodextrin is β-cyclodextrin modified with glycidyl and carboxymethyl groups.

2. The long-lasting weather-resistant and anti-corrosion powder coating according to claim 1, characterized in that: The ultraviolet absorber is one or more of UV-P, UV-9, and UV-531; and / or the antioxidant is one or more of antioxidant 264, bisphenol A, and antioxidant 2246.

3. The long-lasting weather-resistant and anti-corrosion powder coating according to claim 1, characterized in that: The method for preparing the modified cyclodextrin includes the following steps: S1: β-Cyclodextrin was dissolved in an organic solvent under nitrogen protection, activated with sodium hydroxide, and epichlorohydrin was slowly added dropwise to carry out the reaction. After precipitation with methanol, washing and drying, epichlorohydrin was obtained. S2: Dissolve glycidyl β-cyclodextrin in water, add monochloroacetic acid, adjust the pH to 10-11, and then react. After precipitation with ethanol, washing, and drying, the product is obtained.

4. The long-lasting weather-resistant and anti-corrosion powder coating according to claim 3, characterized in that: In step S1, the mass ratio of β-cyclodextrin to epichlorohydrin is 1:(0.3-0.4).

5. The long-lasting weather-resistant and anti-corrosion powder coating according to claim 3, characterized in that: In step S2, the mass ratio of epioxypropylated β-cyclodextrin to monochloroacetic acid is 1:(0.1-0.2).

6. The long-lasting weather-resistant and anti-corrosion powder coating according to claim 1, characterized in that: The method for preparing the organically modified layered bimetallic hydroxide includes the following steps: A) Dissolve zinc salt and aluminum salt in water, co-precipitate under alkaline conditions, and obtain the precursor by aging, filtration, washing and drying; B) The precursor is pretreated in sodium chloride solution, then reacted with disodium terephthalate aqueous solution, and obtained by filtration, washing and drying.

7. The long-lasting weather-resistant and anti-corrosion powder coating according to claim 6, characterized in that: In step A), the molar ratio of zinc salt to aluminum salt is (2-3.5):

1.

8. The long-lasting weather-resistant and anti-corrosion powder coating according to claim 6, characterized in that: In step B), the concentration of the sodium terephthalate aqueous solution is 0.1-0.5 mol / L.

9. A method for preparing a long-lasting weather-resistant and anti-corrosion powder coating according to any one of claims 1-8, characterized in that: Includes the following steps: First, the modified cyclodextrin, ultraviolet absorber, and antioxidant are dispersed in water to obtain an inclusion solution; then, the organic modified layered bimetallic hydroxide is dispersed in water to obtain a suspension; the inclusion solution is added dropwise to the suspension, stirred and reacted, and after filtration, washing, and drying, polyester resin, curing agent, titanium dioxide, barium sulfate, leveling agent, and benzoin are added, mixed evenly, melt-extruded, and then cooled and crushed.

10. The method for preparing a long-lasting weather-resistant and anti-corrosion powder coating according to claim 9, characterized in that: The parameters for melt extrusion are: feeding section temperature 80-100℃, melting section temperature 100-120℃, extrusion section temperature 110-130℃, screw speed 300-500rpm, and residence time 30-60s.